A Registry Software for Road Traffic Injury Patients at Apex Trauma Centre in India: An Innovation. Issue Volume 34:Issue s1(2019) (May 2019) - Kaushik, Gaurav; Gupta, Amit; Kumar, Subodh; Soni, Kapil Dev; Sharma, Ankita
Abstract : Introduction: A trauma registry is a disease-specific data collection composed of a file of uniform data elements that describe the injury even, demographics, prehospital information, diagnosis, care, outcomes, and costs of treatment for injured patients. Aim: To establish a trauma registry system on an electronic platform enabling data capturing through Android phones. Methods: A software has been developed for the registry data collection for road traffic injury patients arriving at JPNATC, AIIMS, New Delhi. The software has been designed to use in the Emergency Department on Android phones/laptops with internet access. Result: A detailed registry data set has been prepared to enter prehospital, in-hospital, and post-discharge details of all the admitted patients. This includes demographic data, prehospital data, injury event data, vital signs within 24-hrs of arrival, ED disposition (date and time), operative procedures within 48 hours of arrival, chest x-ray (date and time), CT (date and time), ventilation days, ICU-stay days, hospital disposition (date and time), injury coding data (region, severity level, ISS, AIS, ICD-10) and Others, e.g., first neurosurgical consultation (date and time) and first blood transfusion (date and time). There are two panels for this software; one for user panel and another for the administrative panel. User panel is being used for data collection by the trained data collectors 24/7 at the emergency department on a rotation basis. The administrative panel is accessible to only the investigator or other authorized persons. The administrative panel and user panels are password protected. The entered data is being saved in a spreadsheet in the backend and can be used for periodic data quality check and data analysis. Discussion: There is no trauma registry in India so far for the road traffic injury patients. Present innovation would lay the foundation of national Trauma Registry in India.